Effectiveness of educational interventions on hypertensive patients’ self-management behaviours: an umbrella review protocol - Ireneous N Soyiri; Blessing Onyinye Ukoha-Kalu; Abdulmuminu Isah; Aminu A Biambo; Aliyu Samaila; Mustapha Muhammed Abubakar; Ukoha Agwu Kalu (BMJ Open)
Background Although different educational interventions have been widely used to manage and treat hypertension, alone or in combination with other interventions, there is a significant variation in their claimed effectiveness.Review question/objective The objective of this umbrella review is to determine the effectiveness of educational interventions, alone or in combination with other interventions, for improving blood pressure control and self-management practices among hypertensive patients. The review question is: Do educational interventions, alone or in combination with other interventions, improve self-management practices among patients with hypertension?Methods We will conduct a review of systematic reviews involving studies that implemented educational interventions, alone or in combination with other interventions, designed to change self-care practices among hypertensive patients who are 18 years and above, regardless of their sex and ethnicity. Following the guidelines set forth in the Preferred Reporting Items for Systematic Review and Meta-Analysis statement, a comprehensive literature search will be conducted from September to December 2023 on six electronic databases: MEDLINE, Embase, PsycINFO, CINAHL, Web of Science Core Collection and Google Scholar. Search terms will be developed using database-specific indexed terms and text words derived from the review aim. We will present the effects of the educational interventions, alone or in combination with other interventions, on hypertension self-management practices. We will report the outcome data with 95% CIs for each study. Relative risk, mean differences or ORs will be used, depending on the measuring indices in each study.Ethics and dissemination Ethical approval is not required as this study will use aggregated data from previously published systematic reviews. However, we have registered the protocol in PROSPERO. We confirm that all methods will be performed following the guidelines of the Declaration of Helsinki. The findings from this study will be disseminated through presentations at academic conferences and publication in peer-reviewed international journals.PROSPERO registration number CRD42022375581.